The warrior's character leadership wisdom from West Point's cadet prayer - Snider, Don M. (McGraw Hill, 2013)
As one of America's most honored institutions, West Point has produced some of the greatest leaders in the history of the nation--and the world. For almost a century, West Point's men and women have been both informed and inspired by the "Cadet Prayer"--a simple but profound set of moral precepts for those who aspire to realize in their lives and work as leaders the ideals and principles of West Point.